2017
DOI: 10.17576/3l-2017-2301-06
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Higher Order Thinking Skills via Teaching Practices

Abstract: The birth of the Malaysia Higher Education Blueprint (2015Blueprint ( -2025

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 5 publications
7
42
0
1
Order By: Relevance
“…A good learning is that which is able to cover a series of meaningful activities so that they can be understood, mastered, and applied well (Tiantong & Siksen, 2013). Students should be accustomed to deal with difficult situations in term of complex cognitive conflicts; thus, they can solve problems (Freahat & Smadi, 2014) based on experiences they have had through project activities or case studies provided and laboratory activities practiced (Ganapathy, Singh, Kaur, & Kit, 2017). In addition, good learning also accommodates students cooperatively and collaboratively (İlhan, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…A good learning is that which is able to cover a series of meaningful activities so that they can be understood, mastered, and applied well (Tiantong & Siksen, 2013). Students should be accustomed to deal with difficult situations in term of complex cognitive conflicts; thus, they can solve problems (Freahat & Smadi, 2014) based on experiences they have had through project activities or case studies provided and laboratory activities practiced (Ganapathy, Singh, Kaur, & Kit, 2017). In addition, good learning also accommodates students cooperatively and collaboratively (İlhan, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In other words, teachers need to be very much aware about giving higher order thinking tasks for students as higher level thinking tasks are totally in contrast with lower order tasks that comprise memorizing and translating. Ganapathy, Singh, Kaur & Waikit (2017) claim that though it takes more time to implement higher order thinking skills in the lesson plan, it has positive learning outcomes. The implication of this is that teachers have to work hard for bringing higher order thinking and learning output in the class.…”
Section: Higher Order Thinkingmentioning
confidence: 99%
“…There were about 300 participants from 14 schools in Petaling Utama, Selangor that took part. A research by Ganapathy, Singh,Kaur and Kit (2017) identified that there are several important insights on the potential opportunities of technologies in facilitating higher order thinking but success lies on the tasks that are appropriately designed for promoting the content. This goes at par with the announcement of the Prime Minister Najib Razak on introducing computational thinking and computer science in the curricula for both Malaysian primary and secondary schools starting from 2017 under a #mydigitalmaker movement and 9200 teachers will be trained for this purpose (TodayOnLine, August 11, 2016).…”
Section: Theories Of Action With Meritmentioning
confidence: 99%